THE INFLUENCE OF MARKETING ACTIVITIES IN SOCIAL MEDIA ON PURCHASE INTEREST THROUGH MEDIATION OF CUSTOMER BRAND ENGAGEMENT, SOCIAL BRAND ENGAGEMENT, AND BRAND EQUITY IN HOUSEHOLD EQUIPMENT RETAIL CUSTOMERS IN INDONESIA - Kahlil Gibran Ardha Yassin; Lamhot Henry Pasaribu (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
Global pandemic Covid-19 that has hit people hard contributed to the rise in digital media usage, such as social media. Not only as a medium to communicate among people but more than that, social media become a promotional tool for firms to promote their products or services. This study wants to know the influence of social media marketing activities of home appliances brands in Indonesia to purchase intention through mediating customer brand engagement, social brand engagement, and brand equity. This research uses a quantitative approach with an online survey of 404 sample respondents and analyses it with the Smart-PLS program. The results show social media marketing activities positively influence all mediation variables (consumer brand engagement, social brand engagement, and brand equity), and purchase intention as a dependent variable get positive influence by customer brand engagement and brand equity. Only social brand engagement has a low positive influence on the dependent variable. For managerial implications, it shows if social media marketing activities its become important to do for firms and less recommended for social brand engagement. Other routes for future research are presented.Keywords : SMMA; Digital; Covid-19; Home appliances; Social media.